2010
DOI: 10.1016/j.bbadis.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Neuron specific metabolic adaptations following multi-day exposures to oxygen glucose deprivation

Abstract: Prior exposure to sub toxic insults can induce a powerful endogenous neuroprotective program known as ischemic preconditioning. Current models typically rely on a single stress episode to induce neuroprotection whereas the clinical reality is that patients may experience multiple transient ischemic attacks (TIAs) prior to suffering a stroke. We sought to develop a neuron enriched preconditioning model using multiple oxygen glucose deprivation (OGD) episodes to assess the endogenous protective mechanisms neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 78 publications
(85 reference statements)
2
36
0
Order By: Relevance
“…OGD is a well-appreciated mitochondrial stress mediated by NMDA receptors, and cell death can be observed after neuron-enriched cultures are exposed to > 30 min of deprivation (61). In these experiments, OGD caused an increase in cell death in all genotypes in a time- dependent manner (one-tailed analysis of variance (ANOVA) p < 0.01; Note: time dependence of this effect is not shown with asterisks so as to highlight gene vs. time effects).…”
Section: Chip Deficiency Results In Increased Neuronal Death Followinmentioning
confidence: 99%
See 1 more Smart Citation
“…OGD is a well-appreciated mitochondrial stress mediated by NMDA receptors, and cell death can be observed after neuron-enriched cultures are exposed to > 30 min of deprivation (61). In these experiments, OGD caused an increase in cell death in all genotypes in a time- dependent manner (one-tailed analysis of variance (ANOVA) p < 0.01; Note: time dependence of this effect is not shown with asterisks so as to highlight gene vs. time effects).…”
Section: Chip Deficiency Results In Increased Neuronal Death Followinmentioning
confidence: 99%
“…We have previously shown that 90 min OGD results in membrane rupture and greater than 80% cell death evidenced as lactate dehydrogenase (LDH) release commencing 10 h after the onset of stress (61). Neuronenriched cultures from rats were exposed to 90 min OGD to analyze levels and trafficking of redox-sensitive molecules, including CHIP.…”
Section: Ogd Increases Mitochondrial Stress-associated Protein Expresmentioning
confidence: 99%
“…The OCP module was tested using cortical cultures from day 18 Sprague-Dawley rats prepared as previously described [19]. Oxygen consumption and lactate production were measured with amperometric modules, and acid production was measured with the Cytosensor® and OCP modules.…”
Section: Instrumentsmentioning
confidence: 99%
“…This instrument has been an invaluable tool for multianalyte microphysiometry, and has been used to study the detection of insulin secretion [17], pathways affected by cholera toxin exposure [18], glucose deprivation on neuronal metabolism [19, 20], and measurement of immunological responses [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…The MAMP has allowed determination of the metabolic effects of toxins[9; 10; 11], neural preconditioning[9; 12], islets stimulation[13], and use of inhibitors to study pathways. [14] In the present study, we employed the MAMP to characterize the metabolic response of macrophages to oxLDL and also examined the effects of L-4F alone and complexed with 1,2-dimyristoyl- sn -glycero-3-phosphocholine (DMPC) on macrophage respiratory burst.…”
Section: Introductionmentioning
confidence: 99%